Specialized Speech Potential in the Field of Medicine (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article is discussed the central object of discussion of the linguo-cognitive talent who has such a set of knowledge and experiences in assessing the socio-cultural and professional competences of the doctor from the situation of consultative communication with the patient. In turn, these competencies indicate that in assessing the communicative activity of the doctor from a linguistic-cognitive point of view, it is necessary to pay attention to his socially specialized speech potential in the field of medicine and the realization of this potential within the framework of communication situations and criteria with patients.